Charge transfer in slow collisions of O8+ and Ar8+ ions with H(1s) below 2keV∕amu - Lee, Teck-Ghee; Hesse, M.; Le, Anh-Thu; Lin, C. D. (My University, 2004)
We calculated the charge-transfer cross sections for O8++H collisions for energies from 1eV∕amu to 2keV∕amu, using the recently developed hyperspherical close-coupling method. In particular, the discrepancy for electron capture to the n=6 states of O7+ from the previous theoretical calculations is further analyzed. Our results indicate that at low energies (below 100eV∕amu) electron capture to the n=6 manifold of O7+ becomes dominant. The present results are used to resolve the long-standing discrepancies from the different elaborate semiclassical calculations near 100eV∕amu. We have also performed the semiclassical atomic orbital close-coupling calculations with straight-line trajectories. We found the semiclassical calculations agree with the quantal approach at energy above 100eV∕amu, where the collision occurs at large impact parameters. Calculations for Ar8++H collisions in the same energy range have also been carried out to analyze the effect of the ionic core on the subshell cross sections. By using diabatic molecular basis functions, we show that converged results can be obtained with small numbers of channels.